Struma ovarii with serous cyst adenoma: a rare case report - Anjali; Mani, Mrinalini; Nidhi, Anupam; Bansal, Disha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Struma ovarii is a rare ovarian teratoma of mono dermal variant constituting 1-4% of all benign teratoma. Any ovarian teratoma is called struma ovarii only when it consists of at least 50% thyroid tissue. Its coexistence is extremely uncommon with serous cystadenoma with only a handful of cases reported till date. Hereby we present a rare case of 36 years old women with hypothyroidism presented to our OPD with pain abdomen for past 3 months and ovarian mass. Clinicoradiologically possibility of an endometrioma was considered. Histopathological examination revealed coexisting double pathologies; of which struma ovarii was an incidental finding. This case is important, not only being rare, but it also highlights the importance of careful and extensive histopathological examination even in a seemingly simple cystic lesion of the ovary to avoid missing concomitant focal pathologies.